2020
DOI: 10.1096/fj.202000502
|View full text |Cite
|
Sign up to set email alerts
|

Existing bitter medicines for fighting 2019‐nCoV‐associated infectious diseases

Abstract: The sudden outbreak of COVID-19 has led to more than seven thousand deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…4 In the 1990s, histamine-2 receptor antagonists including famotidine were shown to inhibit human immunodeficiency virus replication without affecting lymphocyte viability in vitro. 2,5,6 There are limitations to the study. It was observational, and we cannot exclude the possibility of unmeasured confounders or hidden bias that account for the association between famotidine use and improved outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the 1990s, histamine-2 receptor antagonists including famotidine were shown to inhibit human immunodeficiency virus replication without affecting lymphocyte viability in vitro. 2,5,6 There are limitations to the study. It was observational, and we cannot exclude the possibility of unmeasured confounders or hidden bias that account for the association between famotidine use and improved outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The protein targets of SARS-CoV-2 included were spike glycoproteins, RdRp, endoribonuclease, nucleocapsid proteins, envelope protein, membrane protein, and non-structural protein and provides new structural insights for drug repurposing of drugs against COVID-19 [ 46 ]. A study suggested that Chloroquine probably used as one of the effective therapeutic agents against SARS-CoV-2 based on host-directed therapy, although there are several studies required to confirm their efficiency [ 47 ]. Chloroquine and Hydroxychloroquine are being used in many countries to treat the infection as these antivirals are known to have inhibited viral entry and endocytosis; however, they have not shown 100% effective responses [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no specific treatment for nCoV . Developing a new drug or vaccine is a major challenge; therefore, other antiviral drugs are fast-tracked for testing against nCoV (Li et al, 2020). Recent studies have shown that nCoV is mutating and evolving frequently (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%